A risk score to predict the development of hepatic encephalopathy in a population‐based cohort of patients with cirrhosis. Issue 4 (14th May 2018) - Tapper, Elliot B.; Parikh, Neehar D.; Sengupta, Neil; Mellinger, Jessica; Ratz, David; Lok, Anna S.‐F.; Su, Grace L.
Abstract : Over 40% of patients with cirrhosis will develop hepatic encephalopathy (HE). HE is associated with decreased survival, falls, motor vehicle accidents, and frequent hospitalization. Accordingly, we aimed to develop a tool to risk‐stratify patients for HE development. We studied a population‐based cohort of all patients with cirrhosis without baseline HE (n = 1, 979) from the Veterans Administration from Michigan, Indiana, and Ohio (January 1, 2005‐December 31, 2010) using demographic, clinical, laboratory, and pharmacy data. The primary outcome was the development of HE. Risk scores were constructed with both baseline and longitudinal data (annually updated parameters) and validated using bootstrapping. The cohort had a mean age of 58.0 ± 8.3 years, 36% had hepatitis C, and 17% had ascites. Opiates, benzodiazepines, statins, and nonselective beta‐blockers were taken at baseline by 24%, 13%, 17%, and 12%, respectively. Overall, 863 (43.7%) developed HE within 5 years. In multivariable models, risk factors (hazard ratio, 95% confidence interval) for HE included higher bilirubin (1.07, 1.05‐1.09) and nonselective beta‐blocker use (1.34, 1.09‐1.64), while higher albumin (0.54, 0.48‐0.59) and statin use (0.80, 0.65‐0.98) were protective. Other clinical factors, including opiate and benzodiazepine use, were not predictive. The areas under the receiver operating characteristics curve for HE using the four significant variables in baseline and longitudinal models were 0.68 (0.66‐0.70) and 0.73 (0.71‐0.75), respectively. Model effects were validated and converted into a risk score. A score ≤0 in our longitudinal model assigns a 6% 1‐year probability of HE, while a score >20 assigns a 38% 1‐year risk. Conclusion : Patients with cirrhosis can be stratified by a simple risk score for HE that accounts for changing clinical data; our data also highlight a role for statins in reducing cirrhosis complications including HE. (Hepatology 2017).